Intensitas Penggunaan Gadget dengan Kecemasan pada Siswa SMP Negeri 1 Kota Ternate - Siti Umairah; Novi Elisadevi (PELANTAR PRESS, 2025)
The intensity of gadget use that is too frequent in a day or a week will certainly lead to the lives of teenagers who tend to only care about their gadgets rather than doing activities outside the home. The training is based on the use of gadgets, especially smartphones, which are increasingly popular among teenagers, especially students of SMP Negeri 1, Ternate City. This training aims to determine the significance of the intensity of gadget use with anxiety in students of SMP Negeri 1, Ternate City, totaling 35 students. The training technique was carried out through observation, interviews, test scales, and documentation. The pre-test and post-test sampling used was total sampling. Data collection used a Likert scale consisting of two scales, namely the gadget addiction anxiety scale using normality tests, reliability tests, and hypothesis tests. The results of the normality test training variable that for the pretest results the significance value in the significance column is 0.073 because the significance value is more than 0.05, it can be said that the distribution is normal. While the posttest results are known the significance value in the significance column is 0.223 because the significance value is more than 0.05, it can be said that the distribution is normal. Cronbach Alpha reliability value = 0.8720.60 so that from the analysis it can be stated that the Anxiety Pre-Test scale is reliable. The significance value is 0.002, where the testing criteria are if, Sig 0.05 then Ho is accepted if, Sig 0.05 then Ho is rejected. So, 0.002 0.005 which means Ho is rejected and H1 is accepted. So it can be concluded that, psycho education can reduce anxiety in students so that students can use gadgets more positively.